2014
DOI: 10.1186/s12913-014-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the practice of blood film microscopy for detection and quantification of malaria parasites in northwest Ethiopia fit the standard?

Abstract: BackgroundThe diagnosis of malaria in clinical laboratories mainly depends on blood smear microscopy and this technique remains the most widely used in Ethiopia. Despite the importance of blood smear microscopy for patient’s diagnosis and treatment, little effort has been made to precisely determine and identify sources of error in malaria smear microscopic diagnosis and quantification of parasitaemia. The main objective of the present study was to assess the laboratory practices of health care laboratories ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
1
12
1
1
Order By: Relevance
“…However, only 58% and 39.1% of the participants participated in epidemic investigation and refresher trainings. This finding is in sharp contrast with previous study done in Northwest Ethiopia [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, only 58% and 39.1% of the participants participated in epidemic investigation and refresher trainings. This finding is in sharp contrast with previous study done in Northwest Ethiopia [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Malaria incidence has been declining globally in the last decade. However, in countries like Ethiopia, it remains as one of the top health problems and has been reported as one of the three leading causes of morbidity and mortality in the past years [ 3 ]. Efforts to control and eradicate malaria require a strong diagnostic capability, which should allow a prompt detection and treatment of any parasitemia patient.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of blood smear microscopy contributed to failure of the 1950–1960s WHO Global Programme to Eliminate Malaria [ 1 ]. Recent studies have shown that many clinical laboratories use only thin films [ 2 ] with low sensitivity and virtually no quality control on the results [ 3 ], which could affect both to sensitivity and specificity of the diagnostic test. These results could be even poorer when only thin films are prepared in recycled slides in laboratories without quality control and no periodical training for lab technicians[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some parts of Uganda and Kenya, RDTs were found to be effective when used in low endemicity situations, but high false positive error rates occurred in areas with moderately high transmission [ 40 ]. It is worth noting that malaria microscopy is challenging: a study on the standardization of malaria microscopy in health facilities in Ethiopia on the availability of laboratory logistics and technical practices, concluded that most facilities fell below WHO standard [ 41 ]. Gaps were also noted in the continuity of supply of reagents and laboratory supplies for malaria microscopy in some health facilities in Ethiopia [ 42 ].…”
Section: Discussionmentioning
confidence: 99%